Reovirus intermediate subviral particles constitute a strategy to infect intestinal epithelial cells by exploiting TGF-β dependent pro-survival signaling - Stanifer, Megan; Rippert, Anja; Kazakov, Alexander; Willemsen, Joschka; Bucher, Delia; Bender, Silke; Bartenschlager, Ralf; Binder, Marco; Boulant, Steeve (Cellular microbiology, 2016)
Intestinal epithelial cells (IECs) constitute the primary barrier that separates us from the outside environment. These cells, lining the surface of the intestinal tract, represent a major challenge that enteric pathogens have to face. How IECs respond to viral infection and whether enteric viruses have developed strategies to subvert IECs innate immune response remains poorly characterized. Using mammalian reovirus (MRV) as a model enteric virus, we found that the intermediate subviral particles (ISVPs), which are formed in the gut during the natural course of infection by proteolytic digestion of the reovirus virion, trigger reduced innate antiviral immune response in IECs. On the contrary, infection of IECs by virions induces a strong antiviral immune response that leads to cellular death. Additionally, we determined that virions can be sensed by both TLR and RLR pathways while ISVPs are sensed by RLR pathways only. Interestingly, we found that ISVP infected cells secrete TGF-β acting as a pro-survival factor that protects IECs against virion induced cellular death. We propose that ISVPs represent a reovirus strategy to initiate primary infection of the gut by subverting IECs innate immune system and by counteracting cellular-death pathways.